PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS KETERAMPILAN PROSES PADA PEMBELAJARAN IPA MATERI CAHAYA KELAS V SD - Siti Kholizah Panjaitan; Safrida Napitupulu (PENDALAS: Jurnal Penelitian Tindakan Kelas dan Pengabdian Masyarakat, 2021)
This study aims to develop a product of teaching materials in the form of Student Worksheets based on process skills in learning science of light material in the hope of helping students in learning activities. The method used in this research is the development of Research and Development (R&D) by modifying the Brog and Gall development model through five stages including, potential and problems, data collection, product design, design validation, and design revision. The results showed that the Student Worksheet developed was feasible to use, based on validation by media experts an average score of 3.51 in the "Good" category, and teacher validation an average score of 3.55 in the "Good" category.